Avaliação de implantes distais associados a próteses parciais removíveis de extremo livre bilateral em mandíbula: uma revisão sistemática da literatura - Sousa, Yasmim Santos (2018)
The incorporation of osseointegrated implants into the distal extension of Free-End Removable Partial Dentures (FERPDs) has been suggested as an alternative treatment to reduce biomechanical limitations of conventional FERPDs. The purpose of the present review was to critically and systematically evaluate the information available in the literature on bilateral mandibular FERPDs associated with distal implants compared to conventional FERPDs. The electronic search was performed in the PubMed and Cochrane Library until March 2018, using the MeSH (Medical Subject Headings) descriptors: Jaw, Edentulous, Partially; Dental Implants; Dental Prosthesis, Implant-Supported; Denture, Partial, Removable. The search protocol was performed by two reviewers, in a duplicate and independent manner. The inclusion criteria were: publications in the English language; Rehabilitations with Class I removable partial dentures (RPD) associated with implants; in vivo studies ranging from randomized clinical trials to case series; studies describing the characteristics of implants, as well as success / survival, failure, location and attachment systems; and minimum follow-up of 12 months. Duplicates, revisions, laboratory studies, case reports, observation period shorter than 12 months, title and abstract not compatible with the topic addressed, unavailable full-text, implants with immediate loading and short implants, theses, dissertations and book chapters , were excluded. A total of 188 articles were found, of which 06 were included in this review. The characteristics of the studies, the samples, the intervention and the outcome, as well as the methodological quality and patient satisfaction were described and evaluated. It has been found that bilateral FERPD associated with distal mandibular implants may be a viable treatment option compared to conventional prostheses because it offers better biomechanical performance and greater patient satisfaction. However, predictability regarding success, survival and failure of implants is still questionable. Thus, further studies, with an emphasis on randomized long-term clinical trials, are still needed to ensure their indication.